2014
DOI: 10.3390/cells3020438
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 ICP0: An E3 Ubiquitin Ligase That Counteracts Host Intrinsic and Innate Immunity

Abstract: The herpes simplex virus type 1 (HSV-1) encoded E3 ubiquitin ligase, infected cell protein 0 (ICP0), is required for efficient lytic viral replication and regulates the switch between the lytic and latent states of HSV-1. As an E3 ubiquitin ligase, ICP0 directs the proteasomal degradation of several cellular targets, allowing the virus to counteract different cellular intrinsic and innate immune responses. In this review, we will focus on how ICP0’s E3 ubiquitin ligase activity inactivates the host intrinsic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 121 publications
0
58
1
Order By: Relevance
“…We have also observed that following the translocation of IFI16 to the assembly complex, it colocalizes with the tegument protein pp65, indicating that pp65 also plays a relevant role in the export of IFI16 from the nucleus and becomes part of the virus tegument during the maturation step (16). Moreover, in contrast to what has been observed for herpes simplex virus 1 (HSV-1), a member of the Alphaherpesvirinae (27,29,30), IFI16 does not undergo proteolytic degradation during HCMV infection, suggesting that viral or cellular proteins could stabilize and protect IFI16 during virus infection (16,31).…”
contrasting
confidence: 38%
“…We have also observed that following the translocation of IFI16 to the assembly complex, it colocalizes with the tegument protein pp65, indicating that pp65 also plays a relevant role in the export of IFI16 from the nucleus and becomes part of the virus tegument during the maturation step (16). Moreover, in contrast to what has been observed for herpes simplex virus 1 (HSV-1), a member of the Alphaherpesvirinae (27,29,30), IFI16 does not undergo proteolytic degradation during HCMV infection, suggesting that viral or cellular proteins could stabilize and protect IFI16 during virus infection (16,31).…”
contrasting
confidence: 38%
“…By degrading host restrictive factors with its E3 ubiquitin ligase or by directly interacting with host regulatory complexes, ICP0 plays a vital role in disarming host antiviral responses (13,32,33). Because of ICP0's complex biochemical properties, the cooperativity of its functional domains is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune responses are critical in controlling virulence of HSV-1 and many other viruses through a variety of antiviral pathways (4)(5)(6)(7)(8)(9)(10)(11)(12), and viruses have coevolved to counter these host responses (13)(14)(15)(16)(17)(18)(19)(20). Cells detect the presence of incoming virus through pattern recognition receptors (21,22) that, in turn, lead to the activation of pivotal transcription factors such as IRF (5,23) and NF-B (24).…”
mentioning
confidence: 99%
“…Virions then travel in a retrograde direction to the soma, where they may replicate or immediately establish latency, depending partly on the infected neuronal subtype (3). Virions resulting from periodic reactivation events travel in an anterograde direction along the axon, allowing reinfection of the oral epithelium, thereby facilitating viral shedding and host-to-host transmission (2).Innate immune responses are critical in controlling virulence of HSV-1 and many other viruses through a variety of antiviral pathways (4-12), and viruses have coevolved to counter these host responses (13)(14)(15)(16)(17)(18)(19)(20). Cells detect the presence of incoming virus through pattern recognition receptors (21, 22) that, in turn, lead to the activation of pivotal transcription factors such as IRF (5, 23) and NF-B (24).…”
mentioning
confidence: 99%